Cytomorphological pattern of breast lesions diagnosed on fine-needle aspiration cytology in a district hospital in Kashmir valley - Qadri, Shaika; Khan, Subuh Parvez; Farooq, Summyia; Bhat, Abdul Rouf (International Journal of Advances in Medicine, 2022)
Background: Breast lump is the most common presentation of the breast disease. Fine needle aspiration cytology (FNAC) is a simple, rapid and safe, method to diagnose the breast lesions. The objective of this study was to determine the cytomorphological patterns of various breast lesions diagnosed on FNAC. Methods: This study was conducted on 280 patients presenting with breast lump over a period of 3 years. Results: The age range of these patients was from 11-80 years. Female patients were more than male patients. Left breast involvement was more common than the right breast. The cytological diagnosis included benign breast disease (C2-88%), atypical/probably benign (C3-1%), suspicious for malignancy (C4-3%), malignant (C5-8%). Fibroadenoma and invasive ductal carcinoma were most common among benign and malignant lesions respectively. Conclusions: The primary goal of aspiration cytology is to separate malignant lesions from benign ones and it also makes an important tool in guiding further management of a case. So, it is concluded that FNAC should be used as a routine diagnostic procedure due to its cost effectiveness and quick results, thus maximizing the availability of effective health care to patients with breast lesions.